PENGARUH KOMPETENSI DIRI, KOMPETENSI PROFESIONAL DAN KOMPETENSI SOSIAL TERHADAP KINERJA PEGAWAI NEGERI SIPIL (Studi Kasus Pada Ditjen Penyediaan Perumahan Kementrian Pekerjaan Umum Dan Perumahan Rakyat) - Saputra, Verry Ady; Purwanto, P (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
The research aims to test and analyze the influence of Self-Competence, Social Competence and Professional Competence on the performance of employees at the Directorate General of Housing Provision of the Ministry of Public Works and People’s Housing. Design Quantitative research with population of all employees of Directorate General of Housing Provision, Ministry of PUPR Sampling technique is probability sampling type Simple Random Sampling using slovin formula found 186 respondents as sample and data analysis using multiple linear regression. The results of this study show that the influence of self-competence on employee performance is significant and positive, the influence of professional competence on employee performance is significant and positive, the influence of Social Competence on employee performance is significant and positive. Suggestion as input material ie Directorate General of Housing Provision Ministry of Public Works and Public Housing can provide Education and Training that can increase Skill, Narative Ability, and Organize Awareness for employees to improve organizational performance